3D STRUCTURAL MODELING OF NEUTRALIZING SCFV AGAINST GLYCOPROTEIN-D OF HSV-1 AND EVALUATION OF ANTIGEN-ATIBODY INTERACTIONS BY BIOINFORMATIC METHODS - MOZAFAR MOHAMMADI,; FOROOGH NEJATOLLAHI, (International Journal of Pharma and Bio Sciences, 2014)
Structural studies on the interactions between antigens and antibodies are absolutely necessary and beneficial due to the understanding the principles that influence the interactions. In this work, we modeled 3D structure of specific neutralizing single chain variable fragment (scFv) recombinant antibody against glycoprotein-D (gD) of Herpes Simplex Virus-1 (HSV-1), using Modeller 9.11. To get the best alignment result, the ClustalW2 program was also used. The modeled molecule was evaluated by various servers such as ModEval and SAVES. The scFv binding sites were assessed by Pocket Finder and CASTp programs. The interactions between glycoprotein-D antigen and modeled antibody were thoroughly studied using ClusPro 2.0, a protein docking server. The docking results indicated that the neutralizing anti-gD scFv antibody has high affinity for its ligand due to different types of interactions including hydrogen bonds, hydrophobic forces, and salt bridges that taking place between the two molecules.